Occupational stress and coping among portuguese military police officers - Gomes, A. Rui (2016)
This study describes the professional experience of military police officers from the Portuguese Republican National Guard (N = 95). We focused on the main sources and consequences of stress and the coping strategies used to deal with stress. The evaluation protocol included one closed-ended question and four open-ended questions. Data analysis of meaningful text segments was conceptually based and data categorization followed deductive content analysis. Results allowed the identification of 483 meaning units. Factors intrinsic to the job and the relationships at work were the main stressors referred by participants. The consequences of stressors were evident at an individual level, affecting family, psychological, and physical/health domains. The coping strategies used to deal with the main source of stress in the professional career were focused on problem solving (e.g., active confrontation) and emotional regulation (e.g., situation acceptance). Practical implications and future avenues of research with these professionals are discussed.